The Cost of Compliance: Evaluating Safety and Health Regulations in Kenya’s Construction Industry - Legishion, Jacquelyne J.; Wachira-Towey, Isabella N.; K’Akumu, Owiti A. (Journal of the Kenya National Commission for UNESCO, 2025)
The construction industry makes a significant contribution to Kenya’s economic growth by boosting employment, infrastructure, and GDP. Despite the critical importance of managing cost, quality, and time for project success, persistent safety and health issues highlight ongoing failures. Notwithstanding its importance, the cost of safety and health compliance remains under researched. This paper examines the impact of the cost of safety and health compliance in Kenya’s construction sector, filling a gap in the existing literature. Grounded in Systems, Principal-Agent, Public Choice, and Regulatory Capture theories, it employs a pragmatism paradigm and a mixed-methods approach. A sample of 210 safety officers and site supervisors in Nairobi were randomly selected, achieving a 78% response rate. A linear regression analysis assessed the influence of compliance costs on safety and health practices in the Nairobi construction sector, revealing that compliance costs account for 66.9% of the variance (η² = 0.669, β = 0.818, ρ < .001), indicating a significant impact. This study recommends integrating safety and health costs into contract documents such as Bills of Quantities to improve budgeting transparency and regulatory adherence. The inclusion of standardised safety and health line items, such as the procurement of safety equipment and PPE, statutory costs, and the engagement of safety officers, are proposed to enhance the safety culture at worksites. These measures aim to optimise risk mitigation and resource allocation, providing actionable insights for Kenyan policymakers and industry stakeholders.